Volatile compounds from oak, cherry, chestnut and acacia chips: influence of toasting level - Martins, Nuno (2012)
In the present study, the volatile composition of wood chips from several botanical species potentially relevant for oenological purposes, namely acacia (unknown specie), chestnut (Castanea sativa), cherry (Prunus cerasus) and oak (Quercus robur) was studied by GC/MS. In order to evaluate the effect of the toasting process on volatile compounds contents we have extended our study to wood chips from the botanical species described above, subjected to different toasting levels, such as untoasted and medium toast. To achieve this goal, a preliminary step comprising the extraction of the volatile compounds by pressurized liquid extraction (PLE) has been performed followed by the analysis and identifi cation of those compounds by GC/MS. The identifi cation was tentatively achieved attending to the characteristic fragmentation patterns of these compounds and by comparison with those reported in the literature. The determination of linear retention indexes has allowed the confi rmation of those attributions. Within this study, we were able to identify 45 compounds, arising from polysaccharides, lipids, lignin and polyphenols degradation. Additionally, 16 other compounds were identifi ed in the different wood species under study although their origin is not fully known. In general, our results showed differences among the volatile composition of the different botanical species studied in this work and the infl uence of toasting degree was also observed in this study.